Topology optimization of stress-constrained structural elements using risk-factor approach. (November 2019) - Pastore, Tommaso; Mercuri, Valentina; Menna, Costantino; Asprone, Domenico; Festa, Paola; Auricchio, Ferdinando
Highlights: Topology optimization approach to design concrete structural elements. Risk factor-based formulation of stress constraints to handle non-isoresistant materials. Numerical testing considering a broad sample of concrete properties. Comparison with classical Von Mises stress criterion. Abstract: Recent advances in civil engineering and architecture, especially in Digital Fabrication (DF), have enabled the implementation of challenging solutions that yield components with improved and optimized performances. This work proposes an innovative optimization procedure based on an integrated Risk-Factor and Stress-Constrained approach to design concrete structural elements; the algorithm produces lightweight structures while properly taking into account the asymmetrical compression and traction strengths of concrete-like materials. The algorithm is tested over a set of concrete material properties in a simply supported beam configuration. The Risk Factor approach is compared to a classical Von Mises stress condition, showing a more reliable capability in obtaining optimized beams, while handling a wide range of asymmetrical stress constraints.